On Freud's "Observations On Transference-Love." - Fonagy, Peter (Contemporary Freud, 2013)
This is the third volume in the series Contemporary Freud: Turning Points and Critical Issues, published for the InternationalPsychoanalytical Association. Each volume presents a classic essay by Freud with commentaries by prominent psychoanalytic teachersand analysts from different theoretical backgrounds and geographical locations.""Observations on Transference-Love"" may have been inspired, say the contributors, by the unfortunate emotional involvements of two of Freud's colleagues with female patients. In his paper, Freud speaks of the inevitability of ""transference-love"" in every well-c.